A COMBINATION OF ELECTRIC SUBMERSIBLE PUMP (ESP) AND HYDRAULIC JET PUMP AS A NEW ARTIFICIAL LIFT METHOD FOR AN OIL WELL WITH DOWNHOLE WATER SINK COMPLETION - Chandrana Dinata, Randy
Downhole Water Sink (DWS), a type of completion widely known as an effective technique in dealing with water coning issue, may be strongly circumscribed to produce expected rate of oil production due to low reservoir pressure and/or low productivity index (PI) of the reservoir. In relation to this particular limitation, the applicability of artificial lift for DWS completion is one of intriguing research topics in the petroleum industry. A common proposed method is using dual tubing completion installed with ESP in both tubing to increase both oil and corresponding water production rate. Unfortunately, this particular method is extremely limited by the size of ESP and the inner diameter of the casing being used. Another proposed method is installing ESP in single tubing which produces water while oil is produced naturally through the tubing-casing annulus. However, this method is confined to some extent by the maximum natural oil production rate due to the absence of artificial lift method in the oil bearing zone. In relation to those issues, this paper introduces a new artificial lift method designed for DWS completion which is considered more applicable using combination of ESP and Hydraulic Jet Pump. This method may be a solution in promoting higher oil production rate and optimizing the operating condition of a DWS well. While the conventional DWS completion produces water through tubing and oil through tubing-casing annulus, the artificial lift method introduced in this paper uses ESPpressurized produced water as the power fluid for the Jet Pump in which creates suction effect on the top perforation (oil zone) based on the Bernoulli’s principle. Although the introduced method is designed to deal with low reservoir pressure and/or productivity index, this combination of ESP and Hydraulic Jet Pump may also applicable for other reservoir conditions as the effort in acquiring higher oil production rate. This paper examines the optimum design of combination of ESP and Hydraulic Jet Pump. Two complete procedures and model’s implementation examples are presented in this paper in which reflecting the applicability of this method. The results of the design are the optimum number of ESP stages, the type of ESP pump and motor should be chosen, the efficiency of ESP pump and motor, the efficiency of the Hydraulic Jet Pump, the optimum ratio of nozzle to throat area, the total power required and the overall efficiency of the combination of ESP and Hydraulic Jet Pump. Those all design parameters are based on the desired oil production rate and the corresponding water production rate determined by DWS criteria to stabilize the water oil contact in which reducing the water coning risk. A thorough model comparison study demonstrated the capability of the method introduced in this paper to produce a higher oil production rate and deliver higher NPV compared with conventional DWS completion and DWS completion installed with single ESP to ensure the technical applicability and economical viability. In moderate reservoir pressure and moderate Productivity Index (PI) with fixed nozzle-to-throat area ratio case, the new artificial lift method introduced in this paper may increase the oil production rate from 73.3 to 405.1 BOPD, increase the Net Present Value (NPV) per year from $2,304,082 to $12,809,352 and the Pay Out Time (POT) may slightly decreased from 11 days to 10 days. In the high PI and extremely low reservoir pressure case, the reservoir fails to produce aquifer water (0 BWPD) which results in 0 BOPD critical oil production rate. In this particular condition, the method introduced in this paper improves the oil production rate from 0 to 1400 BOPD and NPV increase from -$74,074 to $46,400,414. The oil production increases in both cases may not trigger the water coning issue due to the accommodation of oil production rate and corresponding water production rate based on downhole water sink criteria.